The Dual Role of Oxidative-Stress-Induced Autophagy in Cellular Senescence: Comprehension and Therapeutic Approaches - Pavlos Pantelis; George Theocharous; Nefeli Lagopati; Dimitris Veroutis; Dimitris-Foivos Thanos; Giasemi-Panagiota Lampoglou; Natassa Pippa; Maria-Anna Gatou; Ioanna Tremi; Angelos Papaspyropoulos; Efthymios Kyrodimos; Evangelia A. Pavlatou; et al. (MDPI AG, 2023)
The contemporary lifestyle of the last decade has undeniably caused a tremendous increase in oxidative-stress-inducing environmental sources. This phenomenon is not only connected with the rise of ROS levels in multiple tissues but is also associated with the induction of senescence in different cell types. Several signaling pathways that are associated with the reduction in ROS levels and the regulation of the cell cycle are being activated, so that the organism can battle deleterious effects. Within this context, autophagy plays a significant role. Through autophagy, cells can maintain their homeostasis, as if it were a self-degradation process, which removes the "wounded" molecules from the cells and uses their materials as a substrate for the creation of new useful cell particles. However, the role of autophagy in senescence has both a "dark" and a "bright" side. This review is an attempt to reveal the mechanistic aspects of this dual role. Nanomedicine can play a significant role, providing materials that are able to act by either preventing ROS generation or controllably inducing it, thus functioning as potential therapeutic agents regulating the activation or inhibition of autophagy.